(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In this paper photochromic microcapsules were prepared by in-situ polymerization using melamine formaldehyde resin as wall materials and tetrachloroethylene solution with photochromic materials as core materials. In order to attain a suitable particle size of microcapsules to be used in fabric by blending or coating, high emulsifiers were used to produce smaller oil drop. The factors affecting the properties of microcapsules were discussed in detail, such as emulsification time, PVA concentration and acidification time. The experiments revealed that the average particle size of microcapsules increased firstly then decreased with the increase of emulsification time. The same trend was observed when different concentrations of emulsifiers were used. Acid conditions directly affected the airproof and transparency of microcapsules. Finally, the optimum process condition was determined. The results showed that the particle size of microcapsules ranged from 1 μm to 20 μm and the photochromic blue microcapsules prepared at the optimum process condition could carry the color change quickly and reversibly. The knit fabric with photochromic property was obtained by coating with photochromic blue microcapsules, and the fabric thus formed could change its color quickly and as well as be reversed back to its original color for many times. The knit fabric had good washing fastness and rubbing fastness. Therefore photochromic blue microcapsules showed signs of potential application in the textile field.